Husband victims of marital violence in Nigerian Muslim homes: an Islamic assessment - Hussain-Abubakar, Sherifat; Arikewuyo, Abdus-Sami’i Imam (Penerbit Universiti Kebangsaan Malaysia, 2024)
Marital violence is an abusive behavior that is directed towards a partner by another partner in a marriage relationship. There are abound studies on marital violence against women but scanty ones on men. Contrary to the popular opinion that men are not prone to marital violence, studies revealed that they experienced it, but it was under-reported. Nigerian Muslim men are not excluded from this happening, they are abused by their wives. In recent times, the Nigerian media has been saturated with dreadful cases of marital violence against men, including Muslim men. It is against this backdrop that this study investigates marital violence against Nigerian Muslim husbands. The study examines its patterns and causes in the light of Islam. The study is descriptive and analytical, adopting participatory observation and media reportage as major research instruments. The study reveals that Nigerian Muslim men suffered major, physical, psychological, sexual, financial, and social abuses from their wives. The causes of this trend were identified to be vengeance, jealousy, poverty, and ignorance of Islamic ethical rules. The effects of these abuses constitute threats to the health and subsequent death of the victim. These revelations are antithetical to Islamic marital rules of peaceful cohabitation. Hence, the study recommends a proper understanding of Islamic marital ethics before marriage, and the establishment of Islamic family counseling centers where couples can seek guidance on steps to take, particularly during disputes.